2021
DOI: 10.2147/ceg.s293272
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Integrins for the Treatment of Inflammatory Bowel Disease: Current Evidence and Perspectives

Abstract: Leukocyte trafficking to the gastrointestinal tract is recognized to play a role in the pathogenesis of inflammatory bowel disease (IBD). Integrins are expressed on immune cells and interact with cell adhesion molecules (CAM) to mediate leukocyte trafficking. Blockade of the gut-tropic integrin α4β7 and its subunits has been exploited as a therapeutic target in IBD. Natalizumab (anti-α4) is approved for moderate to severe Crohn’s disease (CD), but its use is limited due to potential risk of progressive multifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“… 573 Currently, the antibody in the highest clinical trial stage is Etrolizumab, targeting integrin β7, which recently carried out a head-to-head comparison, phase III study, with infliximab, approved anti-TNF-α antibody, for the treatment of moderately to severely active ulcerative colitis (GAEDENIA). 574 Overall, the GARDENIA study demonstrated that etrolizumab and infliximab achieved the same efficacy and safety endpoints at weeks 10 and 54. 575 This head-to-head comparison also shows that the safety of the two in long-term results at 1 year is comparable.…”
Section: Challenges and Opportunities: Integrin-targeting Drug Discov...mentioning
confidence: 85%
“… 573 Currently, the antibody in the highest clinical trial stage is Etrolizumab, targeting integrin β7, which recently carried out a head-to-head comparison, phase III study, with infliximab, approved anti-TNF-α antibody, for the treatment of moderately to severely active ulcerative colitis (GAEDENIA). 574 Overall, the GARDENIA study demonstrated that etrolizumab and infliximab achieved the same efficacy and safety endpoints at weeks 10 and 54. 575 This head-to-head comparison also shows that the safety of the two in long-term results at 1 year is comparable.…”
Section: Challenges and Opportunities: Integrin-targeting Drug Discov...mentioning
confidence: 85%
“…Additionally, PF-00547659, a fully human monoclonal antibody targeting MAdCAM-1, has been proved to be welltolerated and effective in inducing remission in patients with moderate to severe UC (103). PN-943 is another emerging orally administered α4β7 antagonist peptide and it has been confirmed that PN-943 is effective for the induction of remission in UC (104). A phase 2 study is ongoing to evaluate the effects of PN-943 (150 and 450 mg twice daily) on moderate to severe UC patients (NCT04504383).…”
Section: Anti-integrin Therapymentioning
confidence: 99%
“…Therefore, the treatment duration was limited to <6 months and there was no case of PML reported. Ontamalimab is a monoclonal IgG2 antibody against MAdCAM-1, thus preventing lymphocyte migration into sites of intestinal inflammation and is efficacious for IBD treatment [4]. Other potential targets of adhesion molecules for the treatment of IBD include intercellular adhesion molecules, vascular cellular adhesion molecule-1, P-selectin, and P-selectin glycoprotein ligand-1 [9].…”
Section: New Drugsmentioning
confidence: 99%